Edukasi Literasi Digital Dalam Penggunaan Smartphone Siswa Kelas V Seklah Dasar Muhammadiyah Tonggalan Klaten - Nisrina Akbar Rizky Putri; Noor Afy Shovmayanti; Ardiansyah Ardiansyah (Universitas Muhammadiyah Klaten, 2024)
Technological progress is still happening on a massive scale and has been felt by all levels of society, including children. The generation of children born in 2010 is often called the Alpha generation, the generation most familiar with technology and internet facilities. Therefore, assistance is needed regarding the use of digital media, in line with what has been carried out by the government regarding the design of the School Literacy Movement (GLS). However, the facts obtained based on test results in the Program International Student Assessment (PISA) state that students in Indonesia have low literacy compared to other ASEAN countries. Poor literacy can impact students' psychology because children's emotions are still unstable. Elementary school students often conclude information without filtering to ensure whether the information received is valid or not. Therefore, it is necessary to raise awareness of digital literacy among students and parents to prepare them before accompanying their children. There is a need for digital literacy education to be provided in schools. The aim of implementing digital literacy for early school students is to help students understand digital literacy related to how students respond to problems in the digital world.